2020
DOI: 10.1038/s41416-020-0792-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel model of liver cancer stem cells developed from induced pluripotent stem cells

Abstract: BACKGROUND: Liver cancer is the second most common cause of cancer-related death. Every type of tumours including liver cancer contains cancer stem cells (CSCs). To date, the molecular mechanism regulating the development of liver CSCs remains unknown. METHODS: In this study, we tried to generate a new model of liver CSCs by converting mouse induced pluripotent stem cells (miPSCs) with hepatocellular carcinoma (HCC) cell line Huh7 cells conditioned medium (CM). miPSCs treated with CM were injected into the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Previously, our group demonstrated that CSCs can be developed from iPSCs in the presence of CM prepared from various cancer cell lines [10][11][12]14]. Since our goal in this study was to reveal the synergistic action of PTX and Sor at low doses for growth inhibition of CSCs, we used our model of CSCs developed from iPSCs [12,14] to assess the effect of the combination at low concentration. The effect of the combination was evaluated on self-renewal, clonogenic, differentiation potential of CSCs, as well as proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, our group demonstrated that CSCs can be developed from iPSCs in the presence of CM prepared from various cancer cell lines [10][11][12]14]. Since our goal in this study was to reveal the synergistic action of PTX and Sor at low doses for growth inhibition of CSCs, we used our model of CSCs developed from iPSCs [12,14] to assess the effect of the combination at low concentration. The effect of the combination was evaluated on self-renewal, clonogenic, differentiation potential of CSCs, as well as proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells, miPS-BT549cmP cells [12] and miPS-Huh7cmP cells [14], were obtained by the conversion of miPSCs (iPS-MEF-Ng-20D-17, Lot No. 012, Riken Cell Bank, Tokyo, Japan), in which the puromycin (puro) resistant gene and green fluorescent protein (GFP) gene were cloned under the control of the Nanog promoter, in the presence of CM from human breast cancer cell line BT549 cells (ATCC HTB-122) and the human liver cancer cell line Huh7 cell line (Riken Cell Bank).…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Currently, we have successfully been developing models for liver, lung, pancreas, and breast CSCs. Our models have given some insights on the differentiation potential of CSCs and their interactions with cancer-associated cells including fibroblasts and immune cells [43,[164][165][166]. We believe that these CSC models with other recent models deriving from normal cells could provide unique tools for future applications of biomaterial 3D scaffold mimicking tumor microenvironment.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%